Modelling a Thermal Diffusion Interface for Robust Fractional Control - Assaf, Riad; Daou, Roy Abi Zeid; Moreau, Xavier (Journal of Applied Nonlinear Dynamics, 2026)
The objective of this work is to review and elaborate an approximation method of the transfer functions of both semi-infinite and finite homogeneous plane thermal diffusive interfaces, in view to use in robust control applications and to obtain accurate time responses. Novel models are proposed based on the fractional order integration found naturally when modelling diffusive interfaces. The models are verified by checking with the existing exact responses. The results obtained in this part of the work show a very good approximation of the transfer functions of the systems when using a rational representation in both frequency and time domains for several inputs such as the impulse and the step.